2016
DOI: 10.1161/jaha.116.004511
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Incidence of Hypertensive Emergencies in US Emergency Departments From 2006 to 2013

Abstract: BackgroundThe incidence of hypertensive emergency in US emergency departments (ED) is not well established.Methods and ResultsThis study is a descriptive epidemiological analysis of nationally representative ED visit‐level data from the Nationwide Emergency Department Sample for 2006–2013. Nationwide Emergency Department Sample is a publicly available database maintained by the Healthcare Cost and Utilization Project. An ED visit was considered to be a hypertensive emergency if it met all the following criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
90
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 28 publications
7
90
2
4
Order By: Relevance
“…Sample of the United States showed that the incidence of adult emergency department visits for acute hypertension increased monotonically in 2006 to 2013 from 170 340 to 496 894. 6 Hypertensive emergencies accounted for 63 406 visits (677 per million adult emergency department visits overall) in 2006 and 176 769 visits (1670 per million) in 2013. A large American cohort of 1588 consecutive patients with acute severe hypertension from the STAT registry was analyzed in 2009.…”
Section: A Recent Report From the Nationwide Emergency Departmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample of the United States showed that the incidence of adult emergency department visits for acute hypertension increased monotonically in 2006 to 2013 from 170 340 to 496 894. 6 Hypertensive emergencies accounted for 63 406 visits (677 per million adult emergency department visits overall) in 2006 and 176 769 visits (1670 per million) in 2013. A large American cohort of 1588 consecutive patients with acute severe hypertension from the STAT registry was analyzed in 2009.…”
Section: A Recent Report From the Nationwide Emergency Departmentmentioning
confidence: 99%
“…Epidemiological and clinical characteristics of hypertensive emergencies and urgencies have been described in the literature. A recent report from the Nationwide Emergency Department Sample of the United States showed that the incidence of adult emergency department visits for acute hypertension increased monotonically in 2006 to 2013 from 170 340 to 496 894 . Hypertensive emergencies accounted for 63 406 visits (677 per million adult emergency department visits overall) in 2006 and 176 769 visits (1670 per million) in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…For example, hypertension consistently ranks as one of the primary reasons to visit a doctor . Hypertension‐related emergency department (ED) visits are also rising, and patients with hypertension have longer hospital stays and incur greater costs …”
Section: Introductionmentioning
confidence: 99%
“…8 Hypertension-related emergency department (ED) visits are also rising, and patients with hypertension have longer hospital stays and incur greater costs. 9,10 Hypertension takes on further national significance as its burden and impact is unequally distributed across the nation's populations. 11,12 Racial and ethnic minorities, particularly African Americans, have higher rates of hypertension morbidity and mortality Some racial/ethnic minorities are more likely to have hypertension and experience increased hypertension-related morbidity and mortality compared to whites.…”
mentioning
confidence: 99%
“…In 15 of these 62 patients (24%), a nonadherence could be demonstrated, and in 21 patients (34%), a partial nonadherence could be demonstrated. Patients with nonadherence or partial nonadherence showed a longer hypertension history (15 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] vs 10 [3][4][5][6][7][8][9][10][11][12][13][14][15] years, P = 0.04) were prescribed more general medication (number 7.1 ± 3.4 vs 3.4 ± 1.8; P < 0.01) as well as antihypertensive drugs (number 2.8 ± 1.1 vs 1.5 ± 0.7, P < 0.01). A potential BP-raising trigger by medications or food interaction was frequently detectable, predominantly with nonsteroidal anti-inflammatory drugs (NSAIDs; n = 38), glucocorticoids (n = 8), antidepressants (n = 10), and licorice (n = 10).…”
mentioning
confidence: 99%